Capture and Catalytic Conversion of Polysulfides by In Situ Built TiO2‐MXene Heterostructures for Lithium–Sulfur Batteries. Issue 19 (25th March 2019) - Jiao, Long; Zhang, Chen; Geng, Chuannan; Wu, Shichao; Li, Huan; Lv, Wei; Tao, Ying; Chen, Zijin; Zhou, Guangmin; Li, Jia; Ling, Guowei; Wan, Ying; et al.
Abstract: The detrimental shuttle effect in lithium–sulfur batteries mainly results from the mobility of soluble polysulfide intermediates and their sluggish conversion kinetics. Herein, presented is a multifunctional catalyst with the merits of strong polysulfides adsorption ability, superior polysulfides conversion activity, high specific surface area, and electron conductivity by in situ crafting of the TiO2 ‐MXene (Ti3 C2 T x ) heterostructures. The uniformly distributed TiO2 on MXene sheets act as capturing centers to immobilize polysulfides, the hetero‐interface ensures rapid diffusion of anchored polysulfides from TiO2 to MXene, and the oxygen‐terminated MXene surface is endowed with high catalytic activity toward polysulfide conversion. The improved lithium–sulfur batteries deliver 800 mAh g −1 at 2 C and an ultralow capacity decay of 0.028% per cycle over 1000 cycles at 2 C. Even with a high sulfur loading of 5.1 mg cm −2, the capacity retention of 93% after 200 cycles is still maintained. This work sheds new insights into the design of high‐performance catalysts with manipulated chemical components and tailored surface chemistry to regulate polysulfides in Li–S batteries. Abstract : An in situ built TiO2 ‐MXene heterostructure through partial oxidation of Ti3 C2 T x nanosheets combines the advantages of large surface area, strong polysulfides capturing ability, high electrocatalytic activity, and conductivity, which enable enhanced capture and catalytic conversion of polysulfides. Consequently, high sulfur mass loading (5.1 mg cm −2 ) cathodes with heterostructure‐graphene interlayers deliver high sulfur utilization and stable cycling performance.